Advancing sustainable and innovative agriculture: An empirical study of farmers' livelihood risks and the green transformation of food production - Zhuoying Fu; Chongmei Zhang; Zeng Huang; Lu Jia; Guanglin Sun; Wei Wang (Journal of Innovation & Knowledge (JIK), 2025)
Green transformation of food production is an important approach for promoting sustainable agriculture. Based on field survey data from Nanjing Agricultural University's Chinese Land Economy Survey, this study innovatively explores the relationship between farmers' livelihood risks and the green transformation of food production. In contrast to previous research, this study employs the finite mixture model to quantify the degree of green production transformation of rice farmers. We apply structural equation modelling to systematically investigate the impact mechanisms of different types of livelihood risks on the green production transformation of rice farmers. The results reveal that livelihood risks affect the green transformation of rice production, with natural risk exhibiting a significant facilitating effect. Conversely, human, social, physical, and financial risks demonstrate significant inhibitory effects. Furthermore, moderating effect tests indicate that agricultural subsidies, agricultural insurance, and agricultural outsourcing services moderate the impact of livelihood risks on the green transformation of rice production. Heterogeneity analysis shows significant differences and implications for farm households with different demographic, production, and business characteristics. The main contribution of this study is providing empirical evidence to help farmers identify and navigate different types of risk and promote agricultural greening and upgrading.
Keywords: O31; O38; O32; 650; Finite mixture modelling; Green rice production; Green transformation of food production; Livelihood risk; Structural equation modelling